Mevalonate Metabolism in Cancer Stemness and Trained Immunity - Gruenbacher, Georg; Thurnher, Martin (Frontiers in Oncology, 2018)
Epithelial mesenchymal transition (EMT) is an important developmental program that promotes remodeling of cells and tissues during embryogenesis and wound healing but also during cancer development and progression. EMT is a reverse differentiation program that generates cells with stem cell properties. Similar dedifferentiation processes towards more stem-like cells can be observed during the development of innate and acquired immunity. Intriguingly, similar metabolic reprogramming that raises mevalonate metabolism to higher levels may drive both, cancer cell EMT and immune cell training for increased responsiveness to secondary stimulation. In this review, we discuss the parallels between the two programs in cancer and immune cells that are both driven by accelerated mevalonate metabolism. To target cancer stem cells without impairing immunity represents a great challenge in the development of novel cancer therapies.